HISTORIA DE LOS CONCEPTOS Y RESPONSABILIDAD POLÍTICA: UN ENSAYO DE CONTEXTUALIZACIÓN - Villacañas Berlanga, José Luís (Res Publica. Revista de Historia de las Ideas Políticas, 2008)
The history of concepts aims to be the scientific witness of a period that was immersed in endemic differences (class, national, international blocs), as a consequence of ideological and revolutionary radicalisation of the modern project and the no less violent reactionary responses. With the history of concepts the last proposal of scientific and political integration, the Weberian one, is left behind. Today, both testimonies are of radical importance in order to avoid new phenomenon of idealogisation, total politicisation and political fundamentalisms.